If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -0.5u = 11 + -1.33u Solving 6 + -0.5u = 11 + -1.33u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '1.33u' to each side of the equation. 6 + -0.5u + 1.33u = 11 + -1.33u + 1.33u Combine like terms: -0.5u + 1.33u = 0.83u 6 + 0.83u = 11 + -1.33u + 1.33u Combine like terms: -1.33u + 1.33u = 0.00 6 + 0.83u = 11 + 0.00 6 + 0.83u = 11 Add '-6' to each side of the equation. 6 + -6 + 0.83u = 11 + -6 Combine like terms: 6 + -6 = 0 0 + 0.83u = 11 + -6 0.83u = 11 + -6 Combine like terms: 11 + -6 = 5 0.83u = 5 Divide each side by '0.83'. u = 6.024096386 Simplifying u = 6.024096386
| 3(-5)+5y=30 | | -12=a+6+5a | | log(x)+log(x-15)=2 | | 5x+20=10(x+2)-5x | | 10x-8=136 | | -10=6n-1-3 | | 4x+6(2x+4)=104 | | -7=7*-1 | | -4n+6n=8 | | 3(0)+5y=30 | | -16t^2+64t=s | | 9+2(4x-6)=-2(7x-1)+7x | | -3x-6(-6x+13)=153 | | f(x)=x^2+16x+28 | | 5x-16=2x+11 | | 3y+12=-28 | | y+4-2=-3 | | 6n-1+2=13 | | factorm^2=56 | | -2-3m+6m=4 | | -2x-2(-6x+8)=104 | | y=x-44 | | g(4)=25-3r | | 2x-3(x-6)=16 | | 4(w-2)=8w+4-2(-4w-3) | | -4x+0=-7 | | 64a^2b-16a^3+18a^2b-9=0 | | 4x-2(x-9)=26 | | X-24=42 | | -4(6)+y=-7 | | 8(12+a)= | | -4x+4(-x-14)=-144 |